Intra-LC microinjection of orexin type-1 receptor antagonist SB-334867 attenuates the expression of glutamate-induced opiate withdrawal like signs during the active phase in rats. (1st January 2017) - Hooshmand, Bita; Azizi, Hossein; Javan, Mohammad; Semnanian, Saeed
Highlights: Intra-LC glutamate microinjection induces the expression of opiate withdrawal-like behaviors. SB-334867 did not affect glutamate-induced withdrawal-like signs during the rest phase. SB-334867 attenuated glutamate-induced withdrawal-like signs during the active phase. Abstract: Opiate withdrawal syndrome is temporally associated with the hyperactivity of locus coeruleus neurons. Previous studies have shown that this hyperactivity, at least in part, results from the activity of excitatory afferents which mainly include the orexinergic neurons of hypothalamus and glutamatergic neurons of paragigantocellularis (PGi) nucleus. The effect of intra LC orexin type 1 receptor antagonism was investigated on expression of glutamate-induced morphine withdrawal-like signs in rats. Regarding the involvement of both orexin and LC in modulation of circadian rhythm, experimental procedures were performed during the rest (day) and the active (night) phases. Male Wistar rats (250–300 g) received escalating doses (6, 16, 26, 36, 46, 56, 66 mg/kg, 2 ml/kg) of morphine sulfate subcutaneously for 7 days. Then, glutamate (100 nM, 200 nl) was microinjected into the LC region and the subsequent behavioral manifestations were visually monitored in both rest and active phases. SB-334867 (as a selective orexin type 1 receptor antagonist) was microinjected into the LC prior to glutamate administration. Results indicate that intra-LC microinjection of glutamate elicits morphine withdrawal-like behavioral signs in rats. It is noteworthy that this effect was significantly suppressed in rats pretreated with SB-334867 only during the active phase. It could be concluded that orexin-A plays a role in expression of glutamate-induced opiate withdrawal-like signs and differential orexinergic tone during the rest and active phases might explain the observed difference in activity of LC neurons.